Working Beyond 80: The Meaning of Work to An Octogenarian in The Workforce - Ma. Mayla Imelda M. Lapa; Laurence L. Garcia; Endrex P. Nemenzo (Jurnal Keperawatan Indonesia, 2020)
There is an increasing share of people aged 50 years and over in the labor market structure and the rapid aging of the global workforce that supports the latter claim but with a little tank of information on qualitative research describing the experiences of a working octogenarian. An octogenarian is a person who is between 80 and 89 years old. This study aimed to investigate the experiences of a working octogenarian in her fieldwork through a qualitative case study analysis. From the interview, the following three themes were revealed: (a) Work as a legacy, (b) Work as an advocacy, and (c) Work as an opportunity. In the first theme, the participant described that she had a laden path and a mission. These had been sustained along with the desire to serve and make a difference. In work as advocacy, she presented the vision to make the lives of the elderly better by making the environment compatible with her aspiration extending beyond the confines of her organization. Considering every work that she took part in as an opportunity to explore and further her vision was the very core of the theme “work as an opportunity.” Working beyond 80 years old becomes possible when one dedicates the undertakings in the fulfillment of the individual’s vision and mission. Abstrak Bekerja di Atas Usia 80: Sebuah Studi Kasus Kualitatif tentang Arti Bekerja bagi Seorang Tenaga Kerja Octogenarian. Terdapat peningkatan jumlah orang yang berusia 50 tahun ke atas dalam struktur pasar tenaga kerja dan penuaan dini dari tenaga kerja global yang mendukung klaim terakhir, namun masih sedikit informasi tentang penelitian kualitatif yang menggambarkan pengalaman seorang oktogenarian yang bekerja. Seorang octogenarian adalah orang yang berusia antara 80 dan 89 tahun. Penelitian ini bertujuan untuk menyelidiki pengalaman seorang oktogenarian yang bekerja pada lapangan kerjanya melalui analisis studi kasus kualitatif. Berdasarkan wawancara, tiga tema berikut terungkap: (a) Bekerja sebagai warisan, (b) Bekerja sebagai advokasi, dan (c) Bekerja sebagai peluang. Pada tema pertama, peserta menggambarkan bahwa dia memiliki jalan yang sarat dan misi. Hal ini telah dipertahankan dengan keinginan untuk melayani dan membuat perbedaan. Pada tema bekerja sebagai advokasi, ia mempresentasikan visi untuk membuat kehidupan lansia menjadi lebih baik dengan membuat lingkungan yang sesuai dengan aspirasinya melampaui batas organisasinya. Mempertimbangkan setiap pekerjaan yang ia ambil sebagai kesempatan untuk mengeksplorasi dan memajukan visinya adalah inti dari tema “bekerja sebagai sebuah peluang.” Bekerja lebih dari 80 tahun sangat mungkin ketika seseorang mendedikasikan upaya dalam pencapaian visi dan misi individu. Kata kunci: aging, gerontologi, octogenarian, pekerja, tenaga kerja